PENGARUH PEMANFAATAN DAUN PANDAN WANGI (Pandanus Amarillyfolius) DAN BATANG SERAI (Andropogon nardus) SEBAGAI INSEKTISIDA ALAMI PEMBASMI KUTU BERAS (Sitophylus oryzae) - Andi Taskirah; Surahman Nur; Andi Dewi Rizka Ainulia Makerra (Universitas Patompo, 2023)
This study aims to determine whether there is an effective effect of fragrant pandan leaf powder (Pandanus amarillyfolius) and lemongrass stems (Andropogon nardus) as natural insecticides on the optimal death of rice bugs (Sitophylus oryzae). This research is an experimental research conducted in the biology laboratory of Patompo University. The experiment was designed using a completely randomized design (CRD) with the concentration of pandan leaf powder (P.amarillifolius) and lemongrass stem (A.nardus) which were varied, namely P0 (0), P1 (60 gram fragrant pandan leaf powder), P2 (60gram lemongrass stem powder), P3 (60gr fragrant pandan leaf powder + 60gr lemongrass stem powder). Based on the results of the study for rice flea mortality, it can be seen that the average of each concentration is P0 (0%), P1 = 56.7%, P2=66.7%, and P3 = 73.3%. Of these concentrations, it can be seen that the best concentration as a natural insecticide for rice flea mortality is P3 with an average mortality of 73.3%. Based on the results of the analysis, it can be seen that the value of F count> F table (6.333> 5.14) or sig value <0.05 (0.033 <0.05), so it can be concluded that H0 is rejected, which means that there is a significant effect of utilizing fragrant pandanus leaves and lemongrass stems as a natural insecticide against rice fleas. So it can be said that fragrant pandanus leaf powder (P.amarillyfolius) and lemongrass stems (A.nardus) can have an effective effect and as a natural insecticide against the death of rice fleas (S.oryzae).Keywords: Pandanus amarillyfolius, Andropogon nardu, Sitophylus oryzae